Isabelle Hallin and supporters outside Saugus Town Hall (Tufts Archival Research Center, 2014)
This date is approximate. photographic prints. (Pictures binder 30 of 49). Caption on back of photograph reads: "A personal triumph was scored by Isabelle Hallin, Saugus high school teacher, as she presented her side of school committee ousting to a crowd of 1200 in Saugus town hall last night. She is seen being cheered by youthful supporters as she left the demonstration."